PERENCANAAN LANSKAP WISATA PESISIR BERKELANJUTAN DI TELUK KONGA, FLORES TIMUR, NUSA TENGGARA TIMUR - Yusiana, Lury Sevita; Nurisjah, Siti; Soedharma, Dedi (http://arl-faperta.ipb.ac.id/, 2011)
Konga Bay is a beautiful natural coastal landscape enriched with local culture and vernacular architecture which is still preserved. There are two objectives of this study, firstly is to propose alternative plan of coastal tourism interpretation trail for KongaBay to support its landscape conservation. Second objective is to plan Konga Bay landscape –in lines with sustainable tourism development, to be a beautiful, pleasant, and long-lasting tourism landscape; as well as giving better living opportunity forlocal community. The study applied descriptive-quantitative method to assess coastal environmental quality, potency of coastal tourism development, acceptability level and local community development in tourism. Those three assessments were integrated to obtained land suitability zone for tourism which was subsequently developed to spatial and circulation programs of coastal tourism in order to plan coastal tourisminterpretation trail and sustainable coastal tourism landscape as well. Tourism zone consisted of (1) main zone for aquatic and terrestrial tourism areas and (2) supporting zone contains welcome and transition areas. Circulation of coastal tourism comprises primary, secondary, tertiary, and tsunami evacuation circulations. Coastal tourism interpretation plan provides three alternatives of interpretative trail. Development plan of Konga Bay coastal tourism landscape includes aquatic and terrestrial tourism landscape.